"Migrated onto the Screen": The impact of the COVID-19 pandemic on the clinical practice of drama therapy. (July 2022) - Atsmon, Amir; Katz, Talia; Pendzik, Susana
Abstract: This article analyzes the impact of the COVID-19 pandemic on the clinical practice of Drama Therapy, considering how a forced shift to the online setting impacted drama therapy's concepts and practice. Anchored in a qualitative analysis of 20 interviews with well-established drama therapy practitioners from 19 different countries, we put forward the notion of four positions of reaction to the online setting: resistance, anxiety, adjustment and fluency . Our discussion of the four positions aims to reflect a composite exploration of practitioners' experiences during various phases of their online work. Importantly, we insist that movement between positions is fluid and dynamic. Building on a prior research examining the use of digital resources before March 2020, our analysis utilizes the metaphor of forced migration to consider the range of experiences and challenges that emerged when online work was no longer a choice amidst the spread of the coronavirus. We hypothesize that practitioners who were able to channel the discipline's creative ethos and recognize that online drama therapy presents a qualitatively different phenomenon (vis-a-vis in-person practice) were best able to experience the fluency position. We speculate that "online drama therapy" may be different from "practicing drama therapy online, " wondering whether it will develop into a new brand of drama therapy, as more and more practitioners and clients "migrate onto the screen". Highlights: Experienced drama therapists reflect on the impact of Covid-19 on clinical practice. Involuntary shift to online work comprises resistance, anxiety, adjustment, fluency. These four positions are dynamic, fluctuating even in the same practitioner. Social support, client response, and ability to process loss affected the positions. Shift to online practice echoed experiences of involuntary migration and exile.